Opportunities to Improve the Quality of Beef Produced under Smallholder Mixed Crop and Rangeland Livestock Production Systems - Yesihak Yusuf Mummed (Advances in Agriculture, 2023)
East African countries contain a substantial proportion of cattle (9.3%, 136.4 million) and small ruminants (12%, 253.4 million) compared to the world’s total livestock population. In this region, more than 70% of the land surface is conducive to raise red meat animals. However, the region has limited share (approximately 1%) of meat products to the world market due to the failure to satisfy the minimal quality standard. Most of livestock farmers in this region are smallholders operating pastoral and mixed crop-livestock production systems. This study looked at reports on the quality of beef produced by smallholder production systems using Ethiopia as an example in order to identify potential and determinants in quality beef production under smallholders production system. In order to achieve this, research station beef quality reports were considered as a standard to compare the instrumental quality of beef reported from oxen and bulls raised by smallholders in mixed crop-livestock systems, ranches, and Hararghe cattle fattening systems. According to the analysis, oxen in the smallholders in the mixed crop-livestock systems produced comparatively lower-quality beef than oxen reared by the smallholders in the Hararghe fattening and bulls reared in the ranch systems, which produced good-quality beef. Improved feed resources are used in the Hararghe cattle fattening systems; oxen are used for draft service for a brief period of time (2.85 ± 0.58 years) and then sold for slaughter relatively at a young age. In pastoral settings, ranches offer options for the effective use of scare feed resources. The primary factors that determine the quality of beef produced from oxen raised in the mixed crop-livestock system were poor-quality feed resources, long-term draft service (6.62 ± 1.92 years), and old age at slaughter. To improve the quality of beef produced from the oxen raised in the mixed crop-livestock system, the practice of smallholder farmers in the Hararghe cattle fattening system needs to be adopted. The adoption of the practice also contributes to reduce the greenhouse gas emissions from the system and convert the subsistence mixed crop-livestock into a market-oriented system.